PREDICTIVE INFLUENCE OF ROLE OVERLOAD, JOB SATISFACTION, AND WORK ENGAGEMENT ON SELF-RATED PSYCHOLOGICAL WELLBEING: A QUANTITATIVE STUDY OF YOUNG WORKING ADULTS - Onuoha, Chibuzor Uchenna; Attah, Thomas (African Journal of Social and Behavioural Sciences, 2023)
Understanding the relationship between job attitudes and employee health outcomes is a key priority of people management practitioners. This present study contributes to expanding the wellbeing literature by examining role overload, job satisfaction, and work engagement influences on self-rated psychological wellbeing among employees in Ondo State. Using a cross-sectional research design, a total of 317 young working adults comprising 160 females (Mean age = 38.25; SD = 9.22) drawn from three large public sector organizations were purposively surveyed in the study. They completed standardized scales of role overload, job satisfaction, work engagement, and psychological wellbeing in the form of a self-report paper and pencil questionnaire. Moderate to high coefficient alpha reliability (α=.52 to α=.74) was reported in a pilot study to establish the cultural relevance of the items in each scale. Results of hierarchical regression analysis showed role overload to significantly and positively predict psychological wellbeing (β =.21, p <.05), and contributed 6% to variance in psychological wellbeing. Job satisfaction (p>.05) and work engagement (p>.05) did not predict psychological wellbeing. The study concludes that it appears challenging job demands may be necessary if the goal is to foster better psychological wellbeing in young working adults, particularly, among those in public sector organizations.